Design of Web-Based Warehouse: A Case Study of Web-Based Project Equipment Inventory System Using Waterfall Method - Gustiawan, Handa; Rian, Hesti; Irfan, Akbar Muhamad (Jurnal Teknologi Informatika dan Komputer, 2026)
Inventory is crucial for a company. The warehouse still uses books to record receipts, expenditures, and stock. Manual inventory management often leads to various problems, such as data accumulation, inconsistencies in stock quantities, late reporting, and the risk of data loss. This study aims to design and build a web-based inventory information system to replace manual recording and improve warehouse management efficiency in a contractor company to address these issues. The research method used is the waterfall method, which includes requirements analysis, design, coding, and testing. The system was developed using the PHP programming language with a MySQL database and an easy-to-use web-based interface. The results show that the system was successfully built with features for managing incoming and outgoing goods, suppliers, customers, and monthly reports. Black Box Testing on the login form produced all valid scenarios as expected. This system has been proven to accelerate the process of recording and generating inventory reports accurately and efficiently.